Learning strategies and contextual factors in adopting office technology by older office workers / Samsudin Wahab and Ismail Hassan - Wahab, Samsudin; Hassan, Ismail (2005)
The nature of office work has changed dramatically in recent years. Most of senior office workers reluctant to learn and use advancement in office technology that could help them improve the productivity of their office. Primary goals of adult education are to promote self-directed attitudes and behavior towards new technology in the workplace. Previous studies have focus on the identification of knowledge and skills that individuals need to successfully adapt to changing work environment (Daley, 1997; Kozlowski, 1995). These changing technology in the office have resulted in many new learning strategies needed by senior office workers. A relatively unexamined area of investigation concerns the nature of senior office workers adopting the technology in their office job. The purpose of this study is to understand how this particular group has gone through the process of adopting technology. The questions to be answered in this research are: What are the opinions of the employees towards technology adoption in the workplaces? What are the problems facing by them when adopting technology in the workplace? What strategy has been used by the participants in adopting the technology; and what were the contextual factors that shape the process of adopting the office technology? This research was carried out qualitatively. Selected older office workers will be interviewed and their responses will be recorded, transcribed, interpreted, and analyzed based on the theme(s) of the research. Data are collected through an in-depth, open-ended interview method. The criteria for selecting the participants are their length of service in their organizations especially in the office, their age, and their gender. Participants were 10 older office workers who work for at least 15 years from variety of departments in Universiti Teknologi MARA, Terengganu. This research found that a formal and informal strategy has been used by the participants. There are family, organization facilities, government policy and personal factors that affect their adaptation ability towards office technology in their workplace.